Feasibility and acceptability of the community-based program: Plan Ahead. (3rd April 2023) - Lee, Jeong Eun; Kim, Dahee; Kahana, Eva; Kahana, Boaz
Abstract: Objectives: In this article, we assess the feasibility and acceptability and the effect of the Plan Ahead for community dwelling older adults. In addition, we investigated the effects of the program. In addition, we aimed to examine whether the completion of the specific Future Care Planning depended on the participants' competence level. Methods: In this single group feasibility study, trained facilitators delivered the program to a sample of 234 community-residing older adults. Participants completed both pre, post assessments about the acceptability of the program and their completion of the recommended future care planning activities. Results: Based on participant's report on the usefulness and satisfaction of the program after the completion of the program, we found that participants reported high levels of acceptance of the program. Participation rates also confirmed the feasibility of the program. In terms of effects of program implementation, statistically significant changes were noted for several outcomes, such as resource building and FCP activities. In particular, we found that these gains were particularly robust for participants in the low competence group. Conclusion: Pilot program results suggest the feasibility of a short community program enhancing proactive planning for future care needs among older adults residing in their community.